COURAGE AS SEEN IN WINSTON GROOM’S FORREST GROOM - Gabriel Frans Wagey; Olga Rorintulus; Merlin Maukar (KOMPETENSI, 2021)
The purpose of the study is to reveal about courage as seen in Winston Groom's Forrest Gump. The design of the study is qualitative research because the data of this research are in the form of words. The researchers use two kinds of data collection which are the primary source and secondary sources. The primary source is the novel itself and the secondary sources are the materials that the researchers took from books, internet, articles, journals, etc. The researchers use objective approach because the researcher analyzed the courage of the main character in the novel which is one of the internal elements. In analysing the data, researchers do a close reading of the novel and create a coding to help researchers easily find and arrange the research. Because this research uses objective theory, the researcher examines the internal elements of the novel, namely characters, plot, theme and setting. The researchers focus on the character by classifying each character in the novel into two parts, namely round character and flat character. The results of this study can be concluded that the courage of Forrest Gump is seen from two types of courage, namely moral courage and physical courage. First, by moral courage that he dared to face his shortcomings and dared to show his abilities. Second, Forrest also shows physical courage to protect himself and help others. From these results the researcher found that people who have courage can get through all the difficulties in their life.